On the use of intrinsic fluorescence emission ratio in the characterization of hydraulic oil degradation - Ossia, Cn.; Kong, H.; Markova, L. V.; Myshkin, N. K. (ELSEVIER SCI LTD, 2008)
Intrinsic fluorescence emission of oil was used to develop a technique and detector for evaluating oil degradation. Test results for hydraulic oils with and without zinc dialkyldithiophosphates additives and calcium-based dispersant were in conformance with the results of optical emission spectrometry, particulate counts, optical microscopy, total acid number, and viscosity tests. The ratio of intrinsic fluorescence emission was found to be a parameter independent of the concentration of dust and iron contaminants in nonadditive oil. It proved to be dependent on oil chemical degradation, becoming a tool to detect degradation before incipient wear at the tribological interface becomes relevant. The study showed that intrinsic fluorescence emission ratio gives sufficient information to characterize and evaluate oil degradation. (C) 2007 Elsevier Ltd. All rights reserved.